Consultancy report on the South African steel industry : problems and solutions - Moya, Enrico (My University, 2018)
EXECUTIVE SUMMARY Steel consumption and GDP are directly linked to a nation’s development. The more steel a country uses per head, it has been found, the greater the development of that nation. South Africa (SA) has not been demanding the amount of steel required for rapid growth in recent years, with consumption sluggish, and the largest monopolistic supplier of steel not producing to efficient economies of scale. This has impacted the downstream steel industry, as midstream steel suppliers must produce efficiently to create a cost-effective product. Furthermore, steel mills produce with outdated technology and are unable to compete with the quality and price of international steel, which often comes from China. This has led to the Government introducing protectionist barriers on international steel, especially that coming from China. These include, but are not limited to a 10% tariff on all imported steel, with certain steel products receiving a further safeguard of 12%. These protectionist barriers assist large steel producers such as ArcelorMittal SA (AMSA) as they allow AMSA to compete with international steel makers at higher price in the domestic market. However, the concern is that these protectionist measures have not been uniformly distributed across other value-added sectors in the steel industry viz. the downstream which are the manufacturers of end-user steel products. The downstream must compete with international products which are produced at a much lower cost internationally, in its own domestic market. Furthermore, it is difficult to consider exports of downstream steel goods to international markets because these goods are simply too expensive. What has been suggested is that if AMSA is not willing to reinvest and produce at globally competitive prices, then they should be ‘shut down’ in favour of internationally imported steel. It is argued here that this is an economically and socially bad decision, and leaves SA in a vulnerable position. Some suggestions which are given at the end of this research consultancy report are: to ensure that AMSA is to become a fully SA asset, that real alignment and negotiations occur between various stakeholders in the value chain and finally, that SA considers increasing steel demand by stimulating the economy capital growth projects – such projects include the possibility of a refurbished and world class rail system across the SADC region. Another consideration is to service the steel requirement needs of Sub-Saharan neighbours, who’s GDP’s suggest large steel requirements. This consultancy report proceeds in the following manner. First, the steel industry is considered, after which economic thoughts around protectionism are considered. Secondly these are critically analysed in the context of South Africa with assistance from the perceptions of research participants. Finally, a few suggestions are given on ways to better rectify and fix some of the problems facing the steel industry.
MBA Thesis
Keywords: Steel industry and trade -- South Africa.